Gun owners' assessment of gun safety policy: their underlying principles and detailed opinions - Kathleen Grene; Amani Dharani; Michael Siegel (BMC, 2023)
Abstract Background While gun owners are frequently surveyed, we are not aware of any study that has examined principles held by gun owners that underlie their gun policy opinions, or their opinions about specific provisions of each policy. To find the common ground between gun owners and non-gun owners, this paper aims to answer the following: (1) What underlying principles affects gun owner support for gun policies; (2) how do gun owners' attitudes change depending on the specific provisions within these policies? Methods In May 2022, a survey was administered by NORC at the University of Chicago and completed by adult gun owners (n = 1078) online or by phone. Statistical analyses were performed using STATA. The survey used a 5-point Likert scale to evaluate gun owners' principles and attitudes toward firearm regulation, such as red flag laws, and possible provisions to these policies. Focus groups and interviews were conducted with 96 adult gun owners and non-gun owners to further clarify points in the survey for the former and to ascertain support for the same policies and their potential provisions for the latter. Results The principle that gun owners identified with the most concerned keeping guns out of the hands of those with an increased risk for violence. There was significant overlap among gun owners and non-gun owners on policy support, especially with this central theme that those with a history of violence should be prevented from accessing a firearm. The degree of support for policies was different depending on what provisions were said to be included in the policy. For example, the degree of support for universal background checks ranged from 19.9 to 78.4% depending on the details of the legislation. Conclusion This research demonstrates common ground between gun owners and non-gun owners: It informs the gun safety policy community about gun owners' views and principles on gun safety policy and which policy provisions impact their support for a given law. This paper suggests that an effective, mutually agreed upon gun safety policy is possible.